Legal Basis on Recognition and Enforcement of Decisions of Foreign Courts of the Republic of Uzbekistan (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
Today, it is important to create a strong legal framework for the protection of the rights and interests of entrepreneurs and foreign investors. In this article, the legal basis of the recognition and enforcement of the decisions of foreign courts by the Republic of Uzbekistan is analyzed.